High frequency magnetic properties of polymer-bonded Tb-Dy-Ho-Fe fiber composites. (4th July 2018) - Zhao, Ran; Wang, Bowen; Huang, Wenmei; Yan, Jianwu
ABSTRACT: In order to improve the high-frequency performance of magnetostrictive composites, the work fabricated a polymer-bonded Tb-Dy-Ho-Fe fiber composite. Its magnetic properties were investigated and compared with that of polymer-bonded Tb-Dy-Fe fiber composite. An experimental system was setup to measure the major and minor hysteresis loops of the given magnetostrictive composites at different frequencies. The results showed that Tb-Dy-Ho-Fe fiber composites demonstrates superior magnetic properties, such as lower saturation magnetic field (220 kA/m), smaller coercivity force (5 kA/m) and less dynamic magnetic loss (115 W/m3 at 20 kHz, only 60% of Tb-Dy-Fe fiber composites), compared with Tb-Dy-Fe fiber composites. The proposed composite is suitable for the application of sensing and ultrasonic.